Dignity through creativity in early child`s education: the kindergarten "Lazdynelis" case = Godność poprzez twórczość we wczesnej edukacji dziecka: na przykładzie przedszkola "Lazdynelis" - Rudiene, Renata; Volkovickiene, Vida; Butvilas, Tomas (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The whole idea of this paper spins mainly about one of the main aspects within early child`s education - creativity and its meaning to a child`s psychosocial development. Creativity education, especially based on Reggio Emilia point of view, starts from the very young age and therefore kindergartens as well as families play much significant role to support and develop both dignity and creativity roots in child?s everyday routine. It is stressed that being creative is more like being initiative and innovative - the features that are mainly required by contemporary society.
Keywords: dziecko; kreatywność; godność; wczesna edukacja dzieci; Reggio Emilia - filozofia edukacyjna; child; creativity; dignity; early child`s education; Reggio Emilia educational philosophy